EVALUASI PROGRAM PELATIHAN ICT TERHADAP GURU-GURU DI LPMP JAWA BARAT : Penelitian Evaluasi Dengan Menggunakan Model Evaluasi Kirkpatrick Terhadap Pelatihan Intel Teach Getting Started Di Daerah Terpencil Di Kabupaten Garut - Surya, Rika (2012)
The purpose of this evaluation study was to determine the impact of an increase in skills training to the trainees and their impact on student learning outcomes, by implementing the Kirkpatrick evaluation model. Evaluation study was conducted using a sample of the experimental group and control group. The experimental group is a group of teachers in remote areas in Garut district who have been trained in the Intel Teach Getting Started, while the control group is a group of teachers who have never attended training. Research instruments consisted of tests and questionnaires attitude scale. Implementation of the research carried out in three stages, ie when the training took place, after the training ended and six months after the trainees to implement the results of the training. Results showed that (1) there is a difference in skills between the experimental group and control group, (2) there is a difference in student learning outcomes among students of the experimental group with control group students, (3) there is a reaction against the influence of learning, (4) there is a learning effect on behavior, (5) there is the influence of behavior on the result.